Fashionable nostalgia consumption - Larchenko, V. V. (Littera Verlag, Munich, Germany, 2020)
Nostalgia in consumption is actively used by fashion industry for trend commercialization. At the same time, nostalgia can vary that depends on the purpose, outer circumstances/events, institutions, and so on. Modern overconsumption in the form of fast fashion leads to sustainable consumption in the form of low fashion. Both of these forms have nostalgia for the past, but new coronavirus situation leads to nostalgia for the modern shopping practices of fast fashion.
Keywords: nostalgia; consumption; fashion; brand; trend